KEWENANGAN OMBUDSMAN PERWAKILAN PROVINSI RIAU DALAM MENANGANI LAPORAN DUGAAN MAL ADMINISTRASI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA PEKANBARU TAHUN 2022 - Fazri, Rizkylah; ', Ishak (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This paper discusses the authority of the Ombudsman Representative of Riau Province in receiving reports and follow-up reports on alleged maladministration of the Population and Civil Registration Office of Pekanbaru City. Interestingly, Mal administration that rampantly occurred in 2022 based on incoming reports was carried out by the Regional Government and one of the most reported agencies was the Disdukcapil Pekanbaru City. The purpose of this research is to find out how the authority to handle maladministration by the Ombudsman Representative of Riau Province at the Disdukcapil agency in Pekanbaru City in 2022. This study uses the theory of Authority Philipus m. Hadjon (2002). For the research approach, using a qualitative approach with the type of research is descriptive. This research is located in Pekanbaru City. The type of data is divided into two, namely primary data with Purposive informant data collection techniques and secondary data in the form of cooperation documentation which is analyzed using qualitative data according to Miles and Huberman. The results showed that the Ombudsman Representative of Riau Province has exercised its authority in accordance with the law and regulations to handle allegations of maladministration in Disdukcapil Pekanbaru City in 2022. The Ombudsman Representative of Riau Province provides recommendations and directions to improve public services and mediates and handles reports effectively. The Ombudsman's authority includes attribution (based on law) in accordance with Law No. 37 of 2008 concerning the Ombudsman of the Republic of Indonesia in resolving reports of alleged maladministration of protracted delays, not providing services, and procedural irregularities. Mandate, positions that handle reports with areas of duties that include receiving reports, verification, examination, and prevention of reports, and delegation includes the division of tasks and determination of the performance of the Ombudsman Representative of Riau Province in handling reports of alleged mal administration. The inhibiting factors are the lack of human resources owned by the Ombudsman of Riau Province and the lack of understanding from service users of Disdukcapil Pekanbaru City about reporting alleged maladministration to the Ombudsman of Riau Province. Keyword : Authority, Public Service, Ombudsman.